2021
DOI: 10.1038/s41598-021-94508-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of pterostilbene through p53 and cell cycle in mouse lung of squamous cell carcinoma model

Abstract: Cell proliferation and cell death abnormalities are strongly linked to the development of cancer, including lung cancer. The purpose of this study was to investigate the effect of pterostilbene on cell proliferation and cell death via cell cycle arrest during the transition from G1 to S phase and the p53 pathway. A total of 24 female Balb/C mice were randomly categorized into four groups (n = 6): N-nitroso-tris-chloroethyl urea (NTCU) induced SCC of the lungs, vehicle control, low dose of 10 mg/kg PS + NTCU (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The thickness significantly increased from the PM to the M stage as cell proliferation continued to exceed cell apoptosis 32 , 33 . In fact, increased proliferation of bronchial epithelium was observed in NTCU-induced lung SCC in vivo 16 , 18 . Our findings are in line with a study by Surien et al, who found increased epithelium thickness in BALB/c mice after NTCU treatment 15 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The thickness significantly increased from the PM to the M stage as cell proliferation continued to exceed cell apoptosis 32 , 33 . In fact, increased proliferation of bronchial epithelium was observed in NTCU-induced lung SCC in vivo 16 , 18 . Our findings are in line with a study by Surien et al, who found increased epithelium thickness in BALB/c mice after NTCU treatment 15 .…”
Section: Discussionmentioning
confidence: 97%
“…According to a growing number of studies, chemical-induced cancer in animals is the best model for understanding cancer etiology and carcinogenesis as it closely mimics chronic environmental carcinogen exposure 12 . In this regard, N-nitroso-tris-chloroethylurea (NTCU); a component of nitrosoalkylureas, has been shown to induce lung SCC in mice models with a high degree of similarity and comparable histology to human lung SCC 5 , 13 16 . According to Wang et al, NTCU can introduce the same sequence of lung SCC lesions seen in humans, namely ‘normal-hyperplasia-metaplasia-dysplasia-SCC’ 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Other than the induction of cell senescence, p53, also known as the guardian of the genome, is directly engaged in DNA repair processes such as base excision repair (BER) and nucleotide excision repair (NER) [ 61 ]. Moreover, pterostilbene has been shown to up-regulate the p53 protein expression, to exert a chemo-preventive effect against the carcinogenesis of lung squamous cell carcinoma and hepatocellular carcinoma in mouse models [ 62 , 63 ] . In addition to cell senescence and the DNA repair mechanisms of p53 as a tumour suppressor, p53 can also induce apoptosis cell death via receptor-mediated apoptosis and mitochondria-mediated apoptosis [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…One week later, mice in each group would receive the subcutaneous injection of normal saline or DEX (0.5 mg/kg, 0.1 ml/10 g) every 5 days, and 1 month later, all mice were sacrificed to obtain the tumors to measure the width and length of tumors for calculating the volume using the formula of V = L × W 2 /2, V is the tumor volume, L is the tumor length, and W is the tumor width). Besides, qRT‐PCR was also performed to determine the expression of MALAT1 in tumors, and immunohistochemistry to examine the expression of Ki‐67 and active caspase‐3 according to the previous study 23 …”
Section: Methodsmentioning
confidence: 99%
“…Besides, qRT-PCR was also performed to determine the expression of MALAT1 in tumors, and immunohistochemistry to examine the expression of Ki-67 and active caspase-3 according to the previous study. 23…”
Section: Transwell Assaymentioning
confidence: 99%